Stripes instability of an oscillating non-Brownian iso-dense suspension of spheres. (26th April 2018) - Roht, Y. L.; Ippolito, I.; Hulin, J. P.; Salin, D.; Gauthier, G.
Abstract: We analyze experimentally the behavior of a non-Brownian, iso-dense suspension of spheres submitted to periodic square wave oscillations of the flow in a Hele-Shaw cell of gap H . We do observe an instability of the initially homogeneous concentration in the form of concentration variation stripes transverse to the flow. The wavelength of these regular spatial structures scales roughly as the gap of the cell and is independent of the particle concentration and of the period of oscillation. This instability requires large enough particle volume fractions and a gap large enough compared to the sphere diameter . Mapping the domain of the existence of this instability in the space of the control parameters shows that it occurs only in a limited range of amplitudes of the fluid displacement. The analysis of the concentration distribution across the gap supports a scenario of particle migration towards the wall followed by an instability due to a particle concentration gradient with a larger concentration at the walls. In order to account for the main features of this stripes instability, we use the theory of longitudinal instability due to normal stresses difference and recent observations of a dependence of the first normal stresses difference on the particle concentration.